Is a sustainable city model in Sub-Saharan Africa possible? A study based on the cities of Bissau (Guinea-Bissau) and Ziguinchor (Senegal) - (:unkn) unknown (My University, 2021)
With just over half of the world's population living in cities since 2007, urban spaces seem to have become the places where the challenges of the 21st century are crystallised, from global warming and its consequences to the social and territorial inequalities that are growing every day. The ever-increasing demographic explosion in sub-Saharan Africa and its attendant difficulties are accentuating inequalities. The African population doubles every 25 years. This situation poses the crucial problem of meeting the needs of city dwellers in terms of facilities, networks and planning, sustainable construction, urban planning, land management, sanitation, the circular economy, mobility, transport, access to water, etc. It is in this sense that the local Agendas 21 are part of the local declination of the conclusions of the Rio Conference (1992). Since then, new initiatives for a sustainable city have been put forward all over the world or are being tested in urban development projects. The city is thus gradually being identified as a place of development and experimentation of "good practices" of sustainable development. The objective of this thesis is to contribute significantly to a synthetic basis for decision support and programming of development projects and programmes in Guinea-Bissau and Senegal. Two different but complementary methods were combined. The first was to consult archival documents and conduct field surveys with a few resource persons to complement my fieldwork. The approach was based on a transversal and cross-disciplinary look at the interdisciplinary themes of sustainable development by inserting questions specific to the management of urban development projects and programmes.
Keywords: African Research